The Influence of English in Scientific Articles of Indonesian Language and Literature Education Programs: A Corpus-Based Study - Prayogi, Icuk (Universitas Ahmad Dahlan, 2024)
This corpus-based study investigates the influence of English in scientific articles produced within Indonesian language and literature education programs. Although Bahasa Indonesia functions as the official medium of academic instruction and publication in this context, English continues to play a significant role in shaping the linguistic landscape of scholarly writing. The research aims to identify and classify the types of English influence present in academic texts written in Indonesian, highlighting their frequency and function. Data were drawn from six randomly selected scientific articles and analyzed using AntConc software. The analysis revealed a total of 1,152 English-influenced lexical items across 27,349 tokens, comprising 271 distinct forms. These forms were categorized into six types of influence: adaptation, borrowing, calque (literal translation), neologism, translation, and retention (words kept in English and italicized). Among these, adaptation was the most prevalent type, accounting for 78.23% of all English-influenced items, followed by borrowing and calque. While neologisms and retained English terms occurred less frequently, they still illustrate authors’ engagement with global academic discourse. The findings demonstrate that English significantly influences the lexis of scientific writing in Indonesian, particularly in areas where localized terminology may still be lacking. These results suggest a need for further policy development concerning terminology standardization and language use in academic contexts. This study contributes to ongoing discussions about language contact, bilingual academic writing, and the role of English in non-English-medium higher education systems, especially in linguistically diverse settings such as Indonesia.